PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH, DANA ALOKASI UMUM, HASIL PENGELOLAAN KEKAYAAN DAERAH YANG DIPISAHKAN DAN LAIN-LAIN PENDAPATAN ASLI DAERAH YANG SAH TERHADAP PENDAPATAN ASLI DAERAH PROVINSI JAWA BARAT - Denna Aprilla Ardiyanti; Dirvi Surya Abbas; Seleman Hardi Yahawi; Samino Hendriyanto (Jurnal Ekonomi dan Manajemen, 2022)
The purpose of this study is to determine the effect of regional taxes, regional levies, general allocation funds from the management of separated regional wealth and other legitimate regional original income on regional original income empirical studies of West Java Province. The research time period used is the 2016-2021 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria, 25 districts/cities were obtained. The type of data used is secondary data obtained from situs www.djpk.kemenkeu.go.id. The analytical method used is panel data regression analysis. The results of the study indicate that local taxes and other legitimate local revenue have a significant effect on local original income, regional levies and the results of separated regional wealth management have no significant effect on regional original income.